2019
DOI: 10.1155/2019/9723129
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related MicroRNAs Are Associated with Plaque Stability Calculated by IVUS in Coronary Heart Disease Patients

Abstract: Objectives This study aimed to investigate the association between inflammation-related microRNAs (miR-21, 146a, 155) and the plaque stability in coronary artery disease patients. Methods The expression of miR-21, 146a, and 155 was measured by real-time PCR in 310 consecutive patients. The level of hs-CRP, IL-6, and IL-8 was measured by ELISA. The plaque stability of coronary stenotic lesions was evaluated with intravascular ultrasound (IVUS). Results (1) The levels of hs-CRP, IL-6, and IL-8 were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…A previous study reported that puerarin facilitated the proliferation, migration and invasion of colorectal cancer cells by targeting Numb protein (18). Numb was originally identified as an intrinsic determinant in Drosophila, affecting the cell fate by negatively altering the Notch signaling pathway (17). Numb is predominantly expressed in normal proximal tubules and detected in interstitial cells of fibrotic kidneys (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that puerarin facilitated the proliferation, migration and invasion of colorectal cancer cells by targeting Numb protein (18). Numb was originally identified as an intrinsic determinant in Drosophila, affecting the cell fate by negatively altering the Notch signaling pathway (17). Numb is predominantly expressed in normal proximal tubules and detected in interstitial cells of fibrotic kidneys (31).…”
Section: Discussionmentioning
confidence: 99%
“…miR-31 was also found to directly target the 3'-untranslated region (UTR) sequence of the Numb gene (16). Furthermore, miR-31-5p was reported to promote the proliferation of colorectal cancer cells by targeting the Numb protein (17). Numb is considered an intrinsic determinant in Drosophila, which alters the cell fate by negatively regulating the Notch signaling pathway (18).…”
Section: Introductionmentioning
confidence: 99%
“…60 Interestingly, a study associated miR-146a levels with plaque stability in coronary stenotic lesions. 61 The authors found raised miR-146a levels in human peripheral blood mononuclear cells (PBMCs) from vulnerable plaque group versus those from stable plaque group. 61 Accordingly, miR-146a was also increased in PBMCs samples from CAD patients.…”
Section: Biological Functions Of Mir-146a In Immune Cellsmentioning
confidence: 99%
“…In the literature, many clinical studies assessed circulating miRNA levels in peripheral blood for diagnosing, predicting, and monitoring human diseases (158)(159)(160)(161)(162)(163), including cardiac and vascular disease (CVD) (164)(165)(166)(167)(168)(169). For example, the combination of miR-34a-5p and fibrinogen levels have been reported as a useful tool in differentiating pre-thrombotic status in patients with stable coronary artery disease (165).…”
Section: Emerging Challenge Of Bench Studies For Early Detecting and mentioning
confidence: 99%